Determination of calcium, sodium, potassium and magnesium concentrations in human senile cataractous lenses - Dilsiz, N; Olcucu, A; Atas, M (Wiley-Blackwell, 2000)
Cataractous lenses have been found to have a distribution of the intracellular ionic environment, the concentrations of potassium and magnesium decreasing and the concentrations of sodium and calcium increasing relative to the cytosol of most cells. This arises as a result of changes to lens membrane characteristics causing an increase in lens membrane permeability. These changes have been found to be initiated as a result of normal ageing of the human lens. In this study, total Ca(2+), K(+), Na(+) and Mg(2+) contents have been determined in human normal and cataractous lenses using atomic absorption and flame emission spectroscopy. The normal human lens Ca(2+) is between 0.15 and 0.5 mu mol g(-1) fresh lens weight; in senile cataracts the value increased up to 9.31 mu mol g(-1) (p < 0.0001). The normal levels of Na(+), Mg(2+) and K(+) are 20, 5.5 and 60 mol g(-1) respectively; these changed to 136.10, 3.60 and 9.33 mu mol g(-1), respectively in cataractous senile human lenses (p < 0.002, p < 0.002 and p < 0.01). The remarkable differences in these elements may play some role in cataractogenesis. Copyright (C) 2000 John Wiley & Sons, Ltd.
Keywords: human lens; senile cataract; calcium; sodium; potassium; magnesium; atomic absorption spectrophotometer; flame atomic emission spectrophotometer